2003
DOI: 10.1177/0091270003251147
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double‐Blind, Placebo‐Controlled Comparison of the Analgesic Efficacy of Oxycodone 10 mg/Acetaminophen 325 mg versus Controlled‐Release Oxycodone 20 mg in Postsurgical Pain

Abstract: This randomized, controlled trial compared the analgesic efficacy and safety of the new oxycodone 10-mg/acetaminophen 325-mg formulation (Percocet) for the treatment of acute pain following oral surgery with double the dose of oxycodone alone (controlled-release [CR] oxycodone 20 mg [OxyContin]). A total of 150 male and female patients with > or = 2 full or partial bone-impacted mandibular molars, at least moderate persistent pain, and moderate trauma received a single dose of combination agent, CR oxycodone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 26 publications
1
43
1
Order By: Relevance
“…We observed that the commonly reported opioid side effects 6,[31][32][33][34] were present with both regimens, namely, somnolence, dizziness, pruritus, nausea and vomiting. Respiratory depression, one of the most concerning side effects of opioid medications, was not observed in either group, nor were there any acetaminophen-related side effects, including hepatotoxicity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We observed that the commonly reported opioid side effects 6,[31][32][33][34] were present with both regimens, namely, somnolence, dizziness, pruritus, nausea and vomiting. Respiratory depression, one of the most concerning side effects of opioid medications, was not observed in either group, nor were there any acetaminophen-related side effects, including hepatotoxicity.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies in patients after noncardiac surgery reported good pain control and high patient satisfaction with rapid conversion of iv opioid analgesics to oral immediaterelease or controlled-release oxycodone. [4][5][6] A review of the recent literature 7 suggests that immediate-release and controlled-release oxycodone have similar efficacy in the treatment of noncancer pain and similar side effects. Controlled-release oxycodone may offer the advantage of less frequent dosing, thereby decreasing nursing workload.…”
Section: Conclusion : L'oxycodone Peroral Est Efficace Pour Un Contrômentioning
confidence: 99%
“…Combinations of opioid analgesics, such as oxycodone (OC) or hydrocodone, with the nonopioid analgesic acetaminophen have been used extensively in shortacting formulations such as Percocet* (oxycodone/ acetaminophen) 17 and Vicodiny (hydrocodone bitartrate and acetaminophen) 18 . Such combinations have been shown to be effective in several acute pain models, including postoperative pain and postpartum pain 12,19,20 , and are now recommended as first-line therapy in a number of settings 14,21 .…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…2 For a wide range of patients who do not achieve control of CNCP with standard therapies, the combination of oxycodone/paracetamol at low doses has been efficacious and well tolerated in the short-to medium-term. [7][8][9][10][11][12][13][14][15][16][17] The current study investigates whether this efficacy and tolerability also extends to medium-tolong-term use by analyzing clinical charts from consecutive outpatients remaining in treatment with oxycodone/paracetamol. All patients were still in treatment at the last available follow-upappointment.…”
Section: But Itmentioning
confidence: 99%